Influences of different organic fertilizers on nutrients of humic sandy soil and on the growth of Spinach (Spinacia oleracea L.) - Balláné Kovács, Andrea; Kremper, Rita; Kincses, Ida; Leviczky, Ágnes (Acta Agraria Debreceniensis, 2016)
A greenhouse pot experiment was conducted to compare the effects of manure with different origin (horse, cattle), various bedding materials (straw, sawdust) and diverse doses (30 t ha-1, 60 t ha-1) and the impact of food waste compost on the plant growth and the available plant nutrient content of soil. The study was conducted on humic sandy soil and consisted of 9 treatments in a randomized complete block design with four replications. Spinach (Spinacia oleracea L.) was grown as the test crop. The treatments were: 1. unfertilized control; 2. horse manure with straw (30 t ha-1); 3. horse manure with sawdust (30 t ha-1); 4. cattle manure (30 t ha-1); 5 food waste compost (30 t ha-1); 6. horse manure with straw (60 t ha-1); 7. horse manure with sawdust (60 t ha-1); 8. cattle manure (60 t ha-1); 9. food waste compost (60 t ha-1). Plant growth was monitored for 4 weeks. Shoot and root weights per pot were measured, total biomass weight per pot were counted. On the basis of the results it can be concluded, that among treatments the application of horse manure with straw enhanced spinach growth most significantly compared to other treatments and to the non-treated control, resulted the highest weights of leaves and roots of spinach. At the same time even small dose (30 t ha-1) of this fertilizer caused increased plant available nitrogen and phosphorus of soil and the higher dosage further increased these values. The horse manure with sawdust applied in lower dose did not alter the leaves and roots weights, but higher portion (60 t ha-1) caused significantly decreased plant biomass. The results proved that the bedding material may significantly alter the composition of manure and may change the plant nutrition effect of organic fertilizer. Cattle manure and food waste compost in both applied doses enhanced plant growth. Both fertilizers increased the plant available nitrogen forms and phosphorus content of soil, but cattle manure caused higher increase.